FALTA DE NORMATIVA CLARA RESPECTO DE LA CONTRATACIÓN DE FUNCIONARIOS EN EL SECTOR PÚBLICO. TOMANDO EN CUENTA QUE LA LOSEP ESTABLECE DE FORMA TAXATIVA QUE SOLO SE PODRÁ CONTRATAR HASTA UN PLAZO MÁXIMO DE 24 MESES SIN TOMAR EN CUENTA ÁREAS ESTRATÉGICAS QUE REQUIEREN PERSONAL CALIFICADO - Merino Luna, Elvis Lenin (2016)
For development of a nation regarding its economy comes from productivity industry, which are part of the sectors of the economy, which join this strategic sectors, this should be comprehensive and sustained over time, which is requires a state of excellence, among other things, this means that the state is an example of transparency and probity, efficient use of resources, promoting equal opportunities in the social and adequate guarantees of full competition and defending the rights of all citizens. The pro-State modernization reforms are a factor that boosts economic growth, creating new and better forms of citizen participation and strengthen the capacity of the public sector as the main articulator of efforts to achieve equal opportunity and provide satisfaction to the multiple social demands, hence the importance of public servants in government public administration that ensures and guarantees the right to public servants in terms of job security. Responding to the challenges of development of strategic sectors, it involves developing new and greater capabilities and management tools, especially with the human talent, as a prevailing objective in the relations between the State and public servant, and to be put in place a set of initiatives aimed at providing job guarantees for public servants in particular strategic public sectors, with methodological orientations and concrete tasks as a basis for them to improve their actions and move towards a change in traditional bureaucratic culture.